Academics or Socialization? Indirect Influence of Pre-College Preparation, Alignment and Spirality Among Filipino Pre-Service Teachers - Teddy M Fernandez; Joebert D Ballesteros; Jun S Camara (ASEAN Multidisciplinary Research Journal, 2022)
Should college ensure students’ success? College education is the last phase of a learner’s life prior work productivity and understanding how their prior experiences relate with their present self-efficacy across their chosen careers is vital to nation-building. Using a survey-questionnaire, this study measured the Filipino pre-service teachers’ (n=990) perception of their K to 12 experiences across three independent variables and related it with two dependent variables in terms of social self-efficacy and self-efficacy on academic achievement during the 2nd semester in January 2022 in a large public university in Pangasinan, Philippines. Results revealed a higher number of respondents who claimed that K to 12 has prepared them for college, is aligned with the college curriculum, and that Spiral Progression helped them in their college, than those who did not.  Alignment reported the lowest percentage while Spiral Progression showed the highest. Social Self-Efficacy and Self-Efficacy on Academic Achievement are generally high, but their academic achievement registered significant difference across field of specialization while social self-efficacy remains statistically similar. Findings have implications on social practice in HEIs including curriculum summit, competency mapping, understanding the nature of the learners, and implementation of flexible learning in HEIs in the Philippines.